Primary Malignancy in a Supernumerary Testicle Presenting as a Large Pelvic Mass - Justin Noroozian; Daniel Farishta; Daniel Ballow; Joseph Sonstein; Eduardo Orihuela; Eduardo Eyzaguirre (Case Reports in Urology)
Supernumerary testis, also known as polyorchidism, is a condition characterized by the presence of more than two testes. Another condition of the testes is seminoma, a common cause of testicular germ cell tumor. A 35-year-old male was transferred to our hospital with a diagnosis of abdominal mass causing abdominal pain. On physical exam, he had a palpable undescended left testicle in the left inguinal canal, which was determined to be seminoma. The mass was surgically removed, and the patient underwent chemotherapy. The report discusses his workup, treatment, and outcome. This case illustrates an unusual presentation of supernumerary testis with the extra testis harboring a seminoma. When presented with a case of testicular cancer with no tumor noted in the palpable testes, malignancy in an extranumerary testicle should be considered in the differential.